Lithiasis embedded in the pancreatic bile duct Intrapancreatic choledochotomy with the R. Finochietto technique - Delgado, Bolívar; Trotschansky, José (Cirugía del Uruguay, 1982)
In connection with six observations, the authors make a reviion of R. Finochietto's interpancreatic choledochotomy for he approach of calculi embedded in his portion of the choledochus, emphasizing its implicity and its excellent results.